Diseño e implementación de un sistema de riego presurizado para pastos en la finca Landapo de la parroquia Lauro Guerrero, Cantón Paltas, Provincia de Loja - Gallegos Díaz, Cristian Pedro (2016)
In the period May - November 2015 in the Landapo farm belonging to the Parish Lauro Guerrero Paltas Canton, Province of Loja, design and implementation of a pressurized irrigation system for grass production in an area of 0.35 was made he has; the central objective of the project was to contribute to the efficient management of soil and water resources through the design and installation of a sprinkler system. To physically evaluate the soil samples were taken undisturbed with the aid of cylinders Koppecky 100 cm3; while determining the texture and organic matter, altered samples were taken. For agronomic design, it was calculated irrigation needs of growing grass, for it, Thorthwaite the indirect method was used considering the meteor temperature Catacocha Meteorological Station. With the results of soil analysis (bulk density, moisture content: saturation, field capacity and wilting point); the effective root depth; and maximum irrigation needs are determined, Blade, timing and frequency of irrigation. For the hydraulic design, it was calculated from the hydraulic main and secondary network, the same that were designed by the Hazen-Williams formula. After being installed the irrigation system, it was evaluated by Christiansen uniformity coefficient (Cu) of 80% and uniformity of distribution (UD) 60%. To determine the water surface, it was designed and built a 15,66 m3 reservoir, wherein a flow rate of 0,1 l/s is taken. The main results achieved were as follows: the need for crop irrigation maximum was 1.84 mm / day; soils were physically evaluated as poor; basic infiltration rate was 19,85 mm / h; the irrigation depth was 29,4 mm; the frequency of 12 days and the run time of 186 minutes. The diameter of the primary and secondary pipe was 50 mm. Finally, the energy required for operation of the system was 38 meters water column, obtained through the differential topographic level, which is less than the available energy (42.0 meters water column). Keywords: sprinkler irrigation, agronomy design, hydraulic design, evaluation of uniformity Cu